Accelerated Versus Traditional Rehabilitation After Anterior Talofibular Ligament Reconstruction for Chronic Lateral Instability of the Ankle in Athletes. (June 2014) - Miyamoto, Wataru; Takao, Masato; Yamada, Kazuaki; Matsushita, Takashi
Background: Although several reconstruction procedures for chronic lateral ankle instability using autografts have been reported, all have recommended postoperative immobilization and a nonweightbearing period. Hypothesis: Reconstructive surgery with a gracilis autograft using an interference fit anchoring system for chronic lateral ankle instability enables early accelerated rehabilitation and recovery with a return to activity without requiring immobilization. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 33 patients (33 feet) who underwent reconstruction of the anterior talofibular ligament with a gracilis autograft using interference screws were included; 15 were followed for 4 weeks with postoperative cast immobilization (group I), while 18 were followed with accelerated rehabilitation without immobilization (group A). Clinical and radiological results were evaluated based on the Karlsson and Peterson score, talar tilt angle, anterior displacement of the talus on stress radiography, and time between surgery and return to full athletic activity. Results: The mean Karlsson and Peterson scores before and 2 years after surgery were the following: for group I: 62.3 ± 4.7 (range, 54-72) and 94.4 ± 7.1 (range, 76-100), respectively ( P < .001), and for group A: 64.1 ± 4.8 (range, 57-70) and 91.7 ± 7.7 (range, 74-100), respectively ( P < .001). The mean difference in the talar tilt angle compared with the contralateral side and mean displacement of the talus on stress radiography before and 2 years after surgery were the following: for group I: 8.7° ± 2.6° and 7.7 ± 1.8 mm and 3.8° ± 1.5° and 4.0 ± 1.6 mm, respectively, and for group A: 10.5° ± 3.4° and 8.7 ± 2.1 mm and 4.3° ± 1.8° and 4.3 ± 1.2 mm, respectively. Radiography revealed significantly improved postoperative outcomes in both groups ( P < .0001). No significant differences in the score and any parameters on stress radiography were evident at 2 years after surgery between the groups. The mean time between surgery and return to full athletic activity was significantly higher in group I (18.5 ± 3.5 weeks) than in group A (13.4 ± 2.2 weeks) ( P < .0001). No cases of reinjury were reported, and no differences in athletic performance ability were observed between the groups. Conclusion: Patients in group A returned to full athletic activity 5 weeks earlier than those in group I, demonstrating the advantage of accelerated rehabilitation after surgery.